The status of women in the administration of health sciences libraries: a five-year follow-up study, 1972-1977. - Goldstein, R K (1980)
A follow-up survey was conducted in 1977, five years after a previous survey of head librarians in large biomedical libraries, to assess changes that had occurred in the representation of women in top administrative positions. Results for the 126 libraries that responded are reported in six category groupings, with comparative figures for 1977, 1972, and 1950. Also reported are data on head librarian and associate librarian positions and on the appointment rate of women and men to head librarian posts that became vacant from 1972 to 1977. Despite a large number of vacancies and turnover, which provided an opportunity for change to have occurred, the most striking aspect of the 1977 survey is the similarity of its results to those of the 1972 survey. Women made up over three-fourths of the librarian work force and held considerably less than one-half of the head librarian positions.